Quality of different brands of metronidazole available in jimma town, south west Ethiopia; A cross- sectional pharmaceutical quality study - Teshome Sosengo; Tesfaye Mohammed; Ramanjireddy Tatiparthi (University of Mosul, 2020)
Background: WHO report of 2017 estimates that the rates of substandard and falsified medical products in low- and middle-income countries is approximately 10.5% with an estimated spend of US$ 30.5 billion.Objective: The purpose of the study is to assess the quality of different brands of metronidazole available in Jimma town, Oromia region, South West Ethiopia.Methods: Cross-sectional study was conducted in Jimma town, Oromia regional state, Ethiopia. The study was conducted from May 03 – July 30, 2018. Samples were collected using convenience sampling technique. The samples were analyzed using methods specified in British Pharmacopoeia 2013 and United States Pharmacopoeia 2015.Results: All the seven brands of Metronidazole analyzed for quality passed identity test specification of BP 2013. The three brands of Metronidazole capsules passed weight uniformity and dissolution test specification of USP 2015. The seven brands of Metronidazole passed assay (i.e. drug content) test specification of USP 2015. The highest percentage of drug content, 107.81% and 105.56%, obtained for Metronidazole (generic)(capsule) and Nirmet(injection) respectively. However, statistical comparison of assay of respective brands of the respectivedosage forms at 95% confidence interval indicates that there exists significant difference in assay within and among the brands of the respective dosage forms (p<0.05). All the four brands of Metronidazole injections passed USP 2015 limit for Endotoxin, Endotoxin limit ˂0.35Eu/ml. Two brands of Metronidazole injection, Aldezol and Metris, failed sterility test from the four brands of Metronidazole injections included in the study and hence of poor quality.